Study on the differences in peripheral fatigue responses elicitation effects of bench press training with different loads and tempos based on electromyography and motion sensors - Yan, Bin; Li, Zhicong; Li, Chunwei; Han, Chongyang; Yao, Siqi; Ma, DongDong; Zhang, Wenzhong (Frontiers in Physiology, 2025)
ObjectiveThis study aimed to investigate the effects of bench press training with different loads (60% 1RM vs. 80% 1RM) and tempos (maximal velocity X/0/X/0 vs. medium tempo 2/0/2/0) on peripheral fatigue responses in bodybuilders, assessing the specific roles of neuromuscular activation, metabolic stress, and kinetic performance.MethodsTen experienced male bodybuilders performed four training protocols to exhaustion in a randomized crossover design. Electromyography (EMG) was used to record muscle activation (normalized as %MVIC) and spectral shifts (Median Frequency - MDF) from the pectoralis major, anterior deltoid, and triceps brachii muscles. Biochemical assessment involved measuring blood lactate concentrations pre- and post-exercise to quantify metabolic stress. Motion sensors (Vmaxpro) were employed to capture barbell kinematics—including mean velocity (MV), peak velocity (PV), mean power (MP), peak power (PP), and time under tension (TUT)—providing direct measures of neuromuscular performance and fatigue-related velocity loss.ResultsA significant interaction between load and tempo was found for all fatigue markers (p < 0.05). The combination of high load and fast tempo (80% 1RM, X/0/X/0) induced the most pronounced peripheral fatigue, evidenced by the highest muscle activation (%MVIC) and blood lactate levels, coupled with the greatest declines in MDF (indicating neuromuscular fatigue), velocity, and power output.ConclusionThe interaction of load and tempo critically determines the pattern and magnitude of acute peripheral fatigue. High-load fast-tempo training elicits multifaceted fatigue across neuromuscular, metabolic, and performance domains, whereas a high-load medium-tempo protocol results in less fatigue despite longer TUT. These findings provide a scientific basis for precise fatigue management in resistance programming.